Impaired quality of life in patients with treated acromegaly despite long‐term biochemically stable disease: Results from a 5‐years prospective study. (18th April 2017) - Kyriakakis, Nikolaos; Lynch, Julie; Gilbey, Stephen G.; Webb, Susan M.; Murray, Robert D.
Summary: Objective: Patients with acromegaly demonstrate impaired quality of life (QoL), but data on long‐term QoL changes in treated acromegaly are limited. This study evaluates and identifies factors that influence QoL in patients with long‐term biochemical remission. Design: The study consists of a cross‐sectional arm comparing QoL between patients with treated and controlled acromegaly and healthy controls; and a longitudinal arm assessing QoL changes in patients with biochemically stable disease during 5.7±0.6 years of follow‐up. Patients: A total of 58 patients and 116 matched controls were recruited for the cross‐sectional arm; 28 patients completed the longitudinal arm. Measurements: Three generic questionnaires (Psychological General Well‐Being Schedule [PGWBS], 36‐item Short‐Form [SF‐36], EuroQoL [EQ‐5D]) and the disease‐specific acromegaly QoL questionnaire (AcroQoL) were applied. Results: Quality of life assessment was performed 11.6±8.2 years following diagnosis and treatment of acromegaly. Patients with treated acromegaly had lower QoL scores compared with controls in all questionnaires with the exception of the PGWBS "Anxiety" subscale. The AcroQoL "Appearance" subscale and the "Physical Function" subscales of the remaining questionnaires were the most underscored domains. No difference in the total and subscale scores of all questionnaires was observed between baseline and follow‐up, with the exception of the SF‐36 "Physical Function, " where a decline was found (58.5±24.7% vs 43.1±31.1%; P =.002). However, after adjusting for covariates, no significant change in any of the QoL scores was seen. Duration of IGF‐1/GH control was positively correlated with QoL scores in most questionnaires at baseline, whereas use of GH lowering therapy at the time of QoL assessment was a negative predictive factor of QoL. Conclusion: Patients with biochemically controlled acromegaly demonstrate impaired QoL, which persists despite long‐term disease control. This primarily consists of impaired physical function and secondly of impaired psycho‐social well‐being. Duration of biochemical disease control and current use of GH lowering therapy was the predominant factors determining patients' QoL.